Profit Sharing Dalam Program Water Supply Pada Badan Usaha Milik Desa Pandan Harum Desa Selat - Kadek Feri Perdana Putra; Nyoman Ari Surya Darmawan (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to determine how the application of a profit sharing system in the water supply program at the BUMDes Pandan Harum, Selat Village. The formulation of the problem in this study is "How is the implementation of the profit sharing system in the clean water supply program at BUMDes Pandan Harum Selat Village?". This study uses qualitative methods with data collection techniques, namely observation, interviews, and documentation. The results showed that BUMDes Pandan Harum applied profit sharing to the water management business unit. This profit sharing is carried out to official villages, traditional villages, BUMDes managers and BUMDes Eka Karya Giri Utama Wanagiri as owners of the springs. It is stated in the AD/ART belonging to BUMDes Pandan Harum that Dinas gets 20%, Adat gets 10% from the water management business unit, while for Eka Karya Giri Utama BUMDes it is considered a contribution cost and is included in operational costs in the financial statements made because there is no agreement related to profit sharing between the two parties